Pra Studi Kelayakan Potensi PLTM/PLTA Di Area PT. PJB Unit Pembangkit Brantas - Budiono, Budiono; Wahyudi, Slamet; Sutikno, Djoko (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2011)
In accordance with government policy to further optimize the utilization of renewable energy sources, and the policy of PT. PLN (Persero) to reduce the consumption of primary energy derived from fuel, then the PT Pembangkit Jawa-Bali (PT. PJB) plans to optimize the utilization of water resources in the Area PT. PJB Unit Pembangkitan Brantas that have the potential to be developed into minihyro power plants / hydro power plant with a capacity of under 10.0 MW. One purpose of this study is to anticipate the demand for electricity is increasing every year as well as to reduce dependence on primary energy derived from fossil tend thinning, as well as the concern of PT. PJB to environmental sustainability and clean development.Keywords : Pre-Feasibility Study, Potential of Minihydro Power Plants / Hydro Power Pant.